Pharmacological Characterization of the Discriminative Stimulus of Inhaled 1,1,1-Trichloroethane - Shelton, Keith L. (The American Society for Pharmacology and Experimental Therapeutics, 2010)
The present study examined the involvement of the GABA(A), N-methy-d-aspartate (NMDA), nicotinic acetylcholine, and μ-opioid receptor systems in the transduction of the discriminative stimulus effects of the abused inhalant 1,1,1-trichloroethane (TCE). Sixteen B6SJLF1/J mice were trained to discriminate 10 min of exposure to 12,000-ppm inhaled TCE vapor from air. Substitution and antagonism tests and TCE blood concentration analysis were subsequently conducted. TCE blood concentrations decreased rapidly after cessation of exposure, falling by 66% within 5 min. TCE vapor concentration-dependently substituted for the 12,000-ppm training stimulus. The volatile anesthetic halothane concentration-dependently and fully substituted for TCE. The benzodiazepine midazolam partially substituted for TCE, producing a maximum of 68% TCE-lever selection. The benzodiazepine antagonist flumazenil attenuated midazolam substitution for TCE, but not the discriminative stimulus effects of TCE itself. The noncompetitive NDMA receptor antagonists phencyclidine and dizocilpine failed to substitute for TCE. Nicotine and the central nicotinic receptor antagonist mecamylamine also failed to produce any TCE-lever selection, nor did they antagonize the discriminative stimulus of TCE. The μ-opioid receptor agonist morphine did not substitute for TCE. The opioid antagonist naltrexone failed to antagonize the discriminative stimulus of TCE. Overall, the present results, combined with previous studies, suggest that the discriminative stimulus effects of TCE are mediated primarily by positive GABA(A) receptor modulatory effects though a mechanism distinct from the benzodiazepine binding site.